Sedation-analgesia protocol for the injection of botulinum toxin A in cerebral palsy - Marta Cantador-Hornero; Pilar Jiménez-Espuch; Irene de Torres-Garcia; Manuel Contreras-Jiménez; Gorka Luis Martínez-Mezo; José María Morales de los Santos; María Isabel Fernández-Jurado; Marina Tirado-Reyes (Elsevier, 2019)
Objective: To evaluate the impact of the sedation-analgesia technique on the pain experienced by the patient. Methods: This cross-sectional study was conducted on consecutive patients with cerebral palsy (CP) who underwent infiltration with botulinum toxin A (BoTNA). The patients were divided into 4 different groups according to the analgesic strategy assigned: Group I, without sedation or topical anaesthetic cream; Group II, inhalation of nitrous oxide; Group III, deep intravenous sedation; and Group IV, light sedation with benzodiazepines. Pain was assessed with different scales depending on patient age. Parents were asked to rate their satisfaction with their child's comfort by using a 5-point Likert-type scale. The primary end-point was the proportion of patients that experienced a pain level equal or lower than 2, according to pain scales, in the different study groups. Results: Of the 124 patients included in the study, 56 (45.2%) experienced a pain level ≤ 2. In the Group III a significantly greater proportion of patients were classified with a pain level score ≤ 2, P < .001, as compared with all the study groups, respectively. The BoTNA injection was guided by ultrasonography in 109 (87.9%) patients, and by palpation in 15 (12.1%). Conclusion: The results of this study suggested that, in patients with CP treated with BoTNA injections, the sedation-analgesic strategy had a significant impact on the pain experienced by the subject. Selecting an appropriate analgesic strategy is crucial for reducing the stress associated with the administration of BoTNA injections in children with CP. Resumen: Objetivo: Evaluar el impacto de la técnica sedoanalgésica en el dolor experimentado por el paciente. Métodos: Estudio transversal realizado en pacientes consecutivos con parálisis cerebral (PC) que se infiltraron con toxina botulínica A (OnabotA). Los pacientes fueron divididos en 4 grupos según la estrategia analgésica asignada: Grupo I, sin sedación o crema anestésica tópica; Grupo II, inhalación de óxido nitroso; Grupo III, sedación intravenosa profunda y Grupo IV, sedación ligera con benzodiacepinas. El dolor se evaluó con diferentes escalas según la edad del paciente. Los padres clasificaron su satisfacción con la comodidad de su hijo mediante una escala tipo Likert de 5 puntos. La variable primaria de eficacia fue la proporción de pacientes que experimentaron un nivel de dolor ≤ 2, según las escalas de dolor, en los diferentes grupos de estudio. Resultados: De los 124 pacientes incluidos en el estudio, 56 (45,2%) experimentaron un nivel de dolor ≤ 2. En el Grupo III, una proporción significativamente mayor de pacientes presentó un nivel de dolor ≤ 2, p < 0,001, en comparación con todos los grupos de estudio, respectivamente. La inyección de OnabotA fue guiada por ultrasonografía en 109 (87,9%) pacientes y por referencia anatómica en 15 (12,1%). Conclusión: En los pacientes con PC tratados con infiltraciones de OnabotA, la estrategia sedoanalgésica tuvo un impacto significativo en el dolor experimentado por el sujeto. Seleccionar una estrategia analgésica apropiada es crucial para reducir el estrés asociado con la administración de inyecciones de OnabotA en niños con PC.